Observations on the biology and seasonal variation in feeding of the east coast round herring Etrumeus wongratanai (Clupeiformes), off Scottburgh, KwaZulu‐Natal, South Africa. Issue 3 (22nd February 2019) - Vorsatz, Lyle D.; van der Lingen, Carl D.; Gibbons, Mark J.
Abstract : The basic biology and ecology of the South African east coast round herring Etrumeus wongratanai was investigated from samples of fish collected between 2013 and 2016. This species is short‐lived and reaches a maximum of 3 years of age, with rapid growth in its first year of life. It reproduces from June to December (austral summer) and condition factor was lowest in May through to August and increased from September, probably reflecting the physiological strain before and during spawning. Fish larvae were the most important food items consumed during summer, whereas eucalanid copepods were the most important prey at other times of the year. Stable‐isotope data suggest that there are gradual changes in the trophic level with increasing fish size, δ 15 N and δ 13 C values also differed between seasons. The results obtained here are compared with those of other Etrumeus species, regionally and globally.